1985
DOI: 10.1007/bf01332585
|View full text |Cite
|
Sign up to set email alerts
|

An empirical constitutive equation of integral type for viscoelastic liquids

Abstract: A 5-constant constitutive equation is proposed. The analytical form for the relaxation modulus as a function of flow conditions was chosen based on experimental data for stress-relaxation in solid polymers. The resulting formulae for the material functions in simple and oscillatory shear flow fulfil the empirical Cox-Merz rule as well as other phenomenological relations formulated by Coleman and Markowitz. The theoretical results are compared with experimental data obtained by Han for various polymer melts. Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Expressions (4a, b) differ from those originally published [16] in the assumption that Gy and 2 depend on the first invariant of the tensor product A = Ct-t 12t. It agrees with the principles of representation of symmetrical, isotropic tensor functions [28], since Ct -1 and 12t have been introduced into eq.…”
Section: Theoretical Considerationsmentioning
confidence: 93%
See 3 more Smart Citations
“…Expressions (4a, b) differ from those originally published [16] in the assumption that Gy and 2 depend on the first invariant of the tensor product A = Ct-t 12t. It agrees with the principles of representation of symmetrical, isotropic tensor functions [28], since Ct -1 and 12t have been introduced into eq.…”
Section: Theoretical Considerationsmentioning
confidence: 93%
“…(5) are just the same as those from eq. (4) [16]. It has been found that they describe experimental data for many polymeric systems quite well [16].…”
Section: Correlations Between Materials Functionsmentioning
confidence: 96%
See 2 more Smart Citations
“…polyisobutylene (PIB) solution at 0, 25 and 50°C (Schultheisz and Leigh 2002); polydimethylsiloxane (PDMS) at 0, 25 and 50°C (Schultheisz et al 2003); and high-density polyethylene (HDPE) and polypropylene (PP) melts at 200°C. The data for both melts were recalculated from quantitative material functions resulting from an integral constitutive equation, which was presented much earlier (Steller 1985).…”
Section: Introductionmentioning
confidence: 99%